1993
DOI: 10.1111/j.1365-2249.1993.tb06003.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activin A on IgE synthesis and cytokine production by human peripheral mononuclear cells

Abstract: SUMMARYActivin A not oniy stimulates the synthesis and release of pituitary follicie-stimuiating honnone. but exerts various effects on haematopoietic cetis. embryos, and fibroblasts. In the present study we have examined effects of activin A on lgH synthesis and cytokine production by peripheral blood mononuciear ceiis (PBMt") in normai humans. When PBMC were cultuted in the prcsenee of lL-4. activin A significantiy augmented IgE production induced by IL-4. Activin A did not atlect, however, IgE production fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 23 publications
(13 reference statements)
2
24
0
1
Order By: Relevance
“…This effect of blocking activin A by follistatin was consistent with studies that have shown that activin A stimulates production of these cytokines, and other proinflammatory genes, in human, rat, and mouse mononuclear phagocytes in vitro (22,23,42). These data indicate a crucial role for activin A, and, consequently, for endogenous follistatin, in controlling the severity of acute inflammation and its subsequent actions.…”
supporting
confidence: 88%
“…This effect of blocking activin A by follistatin was consistent with studies that have shown that activin A stimulates production of these cytokines, and other proinflammatory genes, in human, rat, and mouse mononuclear phagocytes in vitro (22,23,42). These data indicate a crucial role for activin A, and, consequently, for endogenous follistatin, in controlling the severity of acute inflammation and its subsequent actions.…”
supporting
confidence: 88%
“…Activin stimulates I-B activation, nuclear translocation of NF-B, and phosphorylation of ERK1/2 and p38 MAP kinase in murine BMMs under basal conditions and when stimulated with the receptor activator of NF-B ligand and/or colony-stimulating factor-1 (23,24). Accordingly, activin has been found to stimulate the production of IL-1␤ and TNF by rat BMMs (19) and IL-1␤, IL-6, and TNF by human monocytes and peripheral blood mononuclear cells (25). However, activin also has been shown to inhibit the conversion of the IL-1␤ precursor to its secreted bioactive form, presumably by inhibiting caspase-1 activity (26), and to inhibit secretion of IL-6 by human endometrial epithelial cells (27) and rat thymocytes (28).…”
Section: Discussionmentioning
confidence: 96%
“…A proinflammatory activity is suggested by the pro-migratory effect of activin on monocytes (Petraglia et al, 1991). Furthermore, activin stimulated the production of pro-inflammatory cytokines in human peripheral blood mononuclear cells (Yamashita et al, 1993) and in rat bone-marrow-derived macrophages (Nüsing and Barsig, 1999). However, anti-inflammatory effects of activin have also been demonstrated.…”
Section: The Role Of Activin In Cancer Developmentmentioning
confidence: 99%